Politik Identitas Agama sebagai Tantangan Pelaksanaan Pesta Demokrasi di Indonesia Tahun 2024: Studi Kasus Pilkada DKI Jakarta 2017 & Pilpres 2019 - Alhidayath Parinduri; Pujiati Pujiati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This article aims to analyze and examine the influence of religious identity on political events within the Democratic Party in Indonesia. Indonesia, a nation that officially recognizes six religions and various belief systems, provides a unique backdrop for this analysis. Employing a qualitative research method with a descriptive approach, the study reveals that politics is intricately intertwined with human existence, particularly in the context of selecting leaders at the national, provincial, and local levels. While politics ideally serves the noble purpose of fostering prosperity, it can deviate when specific identities, such as religious affiliations, are exploited to mobilize voters solely based on their identity. This often leads to divisions within the nation. This article delves into the role of political identity in securing victory for a particular party, shedding light on the challenges and complexities associated with this dynamic.